The Influence of the Wage System, Work Environment and Welfare Benefits on Employee Work Productivity of PT. Samawood Utama Work Industries Tanjung Morawa, Deli Serdang, North Sumatra - Zita Nurfitri Pajrin; Abd. Rasyid Syamsuri; Lukman Nasution; Reza Nurul Ichsan (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
The purpose of this study is to ascertain how the wage system, workplace conditions, and welfare allowances affect the productivity of PT. Samawood Utama Work Industries Tanjung Morawa. 90 workers from PT. Samawood Utama Work Industries Tanjung Morawa made up the study's sample. Validity and reliability tests, the classical assumption test, multiple regression analysis, partial tests (t), simultaneous tests (F), and coefficient of determination are among the analytic methods employed. The analysis's findings showed that the wage variable's t-count value was 5.086 when compared to its t-table value of 1.662. When compared to the t table value of 1.662, the estimated t value for the work environment variable is 6.019. In contrast to the t table value of 1.662, the estimated t value for the Welfare Allowance variable is 3.856. When compared to the 2.71 value in the f table, the estimated f value is 843,927. This demonstrates that employee job productivity is positively and significantly impacted by the wage system, work environment, and welfare allowance at the same time. The value of R square indicates that the coefficient of determination is 0.892, implying that 89.2% of employee productivity is driven by pay, work conditions, and welfare benefits, with the remaining 10.8% being impacted by additional factors not included by this study. Keywords: Wage System, Work Environment, Welfare Allowance, Employee Work Productivity